Cancer survival: left truncation and comparison of results from hospital-based cancer registry and population-based cancer registry - Chen, Jian-Guo; Chen, Hai-Zhen; Zhu, Jian; Shen, Ai-Guo; Sun, Xiang-Yang; Parkin, Donald Maxwell (Frontiers in Oncology, 2023)
Background: Cancer survival is an important indicator for evaluating cancer prognosis and cancer care outcomes. The incidence dates used in calculating survival differ between population-based registries and hospital-based registries. Studies examining the effects of the left truncation of incidence dates and delayed reporting on survival estimates are scarce in a real world application. Methods: Cancer cases hospitalized in Nantong Tumor Hospital during the years of 2002-2017 were traced with their records registered in Qidong Cancer Registry. Survival was calculated using the life table method for cancer patients with the first visit dates recorded in hospital-based cancer registry (HBR) as the diagnosis date (OSH), those with the registered dates of population-based cancer (PBR) registered as the incidence date (OSP), and those with corrected dates when the delayed report dates were calibrated (OSC). Results: Among 2636 cases, 1307 had the incidence dates registered in PBR prior to the diagnosis dates of the first hospitalization registered in HBR, while 667 cases with incidence dates registered in PBR were later than the diagnosis dates registered in HBR. The 5-year OSH, OSP, and OSC were 36.1%, 37.4%, and 39.0%, respectively. The "lost" proportion of 5-year survival due to the left truncation for HBR data was estimated to be between 3.5%-7.4%; and the “delayed-report” proportion of 5-year survival for PBR data was found to be 4.1%. Conclusion: Left-truncation of survival in HBR cases was demonstrated. The pseudo-left-truncation in PBR should be reduced by controlling the delayed reporting and maximizing completeness. Our study provides practical reference and suggestions for evaluating the survival of cancer from HBR and PBR.